Life-cycle assessment of residential-scale grid-connected photovoltaic system in Malaysia based on monocrystalline silicon modules - Atiqah Hamizah Mohd Nordin; Shahril Irwan Sulaiman; Sulaiman Shaari; Rijalul Fahmi Mustapa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Even though PV systems have been promoted as a green form of electrification, such systems are still contributing to environmental impacts after considering life-cycle impact during material extraction, manufacturing processes of its components, installation, operation, and maintenance. This paper presents a life-cycle assessment to quantify the environmental impact of residential-scale grid-connected PV systems in Malaysia using monocrystalline silicon PV module. LCA had been carried out by using OpenLCA 1.8 software, Ecoinvent 3.5 database, and impact assessment method of IMPACT2002+ and CED. The influence of varying system capacity from 3 to 12 kWp, system lifetime of 21, 25 and 30 years, and solar irradiation of 1560.8, 1651.8, & 1935.5 kWh/m2/yr, were investigated. The results revealed that the greenhouse gas emissions rate, cumulative energy demand, and energy payback time of residential-scale grid-connected PV systems in Malaysia ranged from 37.97 to 67.26 g CO2-eq/kWh, 4387.10 to 4699.99 MJ/m2, and 6.37 to 7.90 years, respectively. This study also evaluated indicators of energy return on investment. The overall finding implies that the installation of residential-scale grid-connected PV systems in Malaysia offers significant potential for GHG emissions reduction in the country.